Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Hipertensi Di Puskesmas Sawahan Kabupaten Nganjuk - Kusuma, Febry Hadi; Firdaus, Achmad Dafir; Kurniawan, Andi Surya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The absence of symptoms causes hypertensive patients to tend to ignore and not control hypertension. The family becomes a support system in the lives of hypertension patients who require long-term and continuous care. The aim of the research was to determine the relationship between family support and medication adherence in hypertensive patients at Puskesmas Sawahan Kabupaten Nganjuk. This research design uses correlational analytics with an observational approach. This research was conducted at Puskesmas Sawahan Kabupaten Nganjuk. The sampling technique uses purposive sampling technique. The instrument in this study used a questionnaire containing questions about family support and Morisky medication adherence (MMAS). The sample was selected by consecutive sampling and 30 respondents were obtained. The research results showed that almost half had good family support (46.7%) and most were compliant with taking medication (63.3%). Based on the Spearman's Rho Test statistical test, it shows that the ρ value = 0.002 < α (0.05), which means Ha is accepted so it can be concluded, there is a relationship between family support and adherence to taking medication for hypertension at Puskesmas Sawahan Kabupaten Nganjuk.